Mathematical model of heat transfer in roll caliber - Дем’янченко, Ольга Пантеліївна; Кобильська, Олена Борисівна; Ляшенко, Віктор Павлович (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2019)
A physical model of the thermal process in the roll caliber during the rolling of the tape on a two-roll rolling mill was constructed. A mathematical model of the temperature field of a rolling hollow roll of a rolling state of a cylindrical shape rotating about its axis with constant angular velocity is proposed. The mathematical model takes into account different conditions of heat exchange of the inner and outer surfaces of the roll with the belt and its surrounding environment. The temperature field of a hollow roll of a rolling mill is considered as an initial boundary-value problem for a homogeneous non-stationary heat equation with inhomogeneous, nonlinear boundary conditions, which also depend on the angle of rotation of the roll around its axis. The equation describes the temperature field of the rolls during uncontrolled heat transfer during rolling. It significantly depends on the time and number of revolutions around its axis. With a large number of revolutions of the roll around its axis, a quasi-stationary temperature distribution occurs. Therefore, the simplified problem of determining a quasistationary temperature field, which is associated with a thermal process that is time-independent, is considered further in the work. In this case, the temperature field is described using the boundary value problem in a ring for a homogeneous stationary heat equation with inhomogeneous boundary conditions and heat transfer conditions outside the ring, which lie from the angular coordinate. After the averaging operation, the solution of this problem is reduced to solving the equivalent integral equation of Hammerstein type with a kernel in the form of the Green’s function. The Mathcad computer mathematical system builds the temperature distribution of the roll surface. An algorithm for solving a inhomogeneous problem was developed and the temperature distribution of the roll was constructed.